Synthesis, Characterization, and Application of 2-((3-(Chloromethyl)-benzoyl)oxy)benzoic Acid: A Review - Tjahjono, Yudy; Caroline, Caroline; Foe, Kuncoro; Karnati, Srikanth; Ergün, Süleyman; Esar, Senny Yesery; Wijaya, Hendy; Hadinugroho, Wuryanto; Kusindarta, Dwi Liliek; Wihadmadyatami, Hevi (American Chemical Society, 2022)
Salicylic acid (SA) derivate is well-known for its anti-inflammatory and analgesic activity through cyclooxygenase (COX)-inhibition. Previous studies pointed toward gastric toxicity induced by most salicylic acid derivative compounds, particularly acetylsalicylic acid (ASA). Despite the adverse effect, ASA is still used due to price affordability and additional advantages in preventing platelet aggregation. Recently, a novel salicylic acid derivative called 2-((3 (chloromethyl)benzoyl)oxy)benzoic acid (3-CH2Cl) was introduced as a potential alternative compound to substitute ASA. Preliminary assessment results of COX-2 specificity, toxicity profile, analgesic, anti-inflammatory, and antiplatelet activity have made 3-CH2Cl a promising compound for "new"drug development. This review focuses on the discovery, potential activity, and benefits of 3-CH2Cl and the possible molecular mechanisms of its regulations in health and disease. Thus, this review may prove to be beneficial for the utilization of 3-CH2Cl as a potential alternative drug to substitute ASA. © 2022 The Authors. Published by American Chemical Society.